Interaction between Ellagic Acid from Pomegranate Peel and Corn Starch and Its Mechanism of Inhibiting Starch Digestibility - Shengdan CHEN; Zhiwei YANG (Shipin gongye ke-ji)
Objective: To explore the effect of ellagic acid on the physicochemical properties of corn starch and assess the mechanisms of its interaction and of the change in the digestive properties of the ellagic acid-corn starch complex. Methods: First, the effects of ellagic acid on starch gelatinization viscosity, rheological properties, gelatinization heat properties, and solubility expansion were analyzed using different levels of ellagic acid. The structure of the ellagic acid-corn starch complex was characterized using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and nuclear magnetic resonance spectroscopy (NMRS) to elucidate the interaction mechanism. The in vitro digestion index and enzyme inhibition rate of the complex were analyzed to explore the mechanism of the change in the digestion characteristics of the complex. Results: The addition of ellagic acid increased the peak viscosity of corn starch by 27.33% and promoted its short-term retrogradation. In addition, the storage and loss moduli of corn starch decreased, loss factor was increased, and gel structure of starch paste was weakened. Ellagic acid increased the gelatinization temperature of corn starch and the gelatinization enthalpy decreased from 10.1 to 9.34 J/g. The solubility of corn starch was also increased from 6.86% to 9.65%. In addition, XRD showed that ellagic acid and corn starch did not form a V-type inclusion complex, whereas FTIR showed that the peak near 3400 cm−1 was red-shifted. In the NMR spectrum, the chemical shifts of OH-3, OH-2, and OH-6 moved to the high field, indicating that ellagic acid interacts with starch through non-covalent bonds, especially hydrogen bonds. The resistant starch content in the complex increased from 54.83% to 67.39%, and ellagic acid exhibited significant dose-dependent inhibition of α-glucosidase. However, no significant inhibitory effect on α-amylase was observed. Conclusions: Ellagic acid significantly altered the physicochemical properties of corn starch, and hydrogen bonding was identified as the primary interaction force between ellagic acid and corn starch. The change in the starch structure and inhibitory ability of ellagic acid on α-glucosidase decreased the digestibility of the complex. This study contributes to a deeper understanding of the mechanism of the interaction between ellagic acid and corn starch and the reduction of starch digestibility. In addition, theoretical guidance is provided for the development of novel starch-based foods with a low glycemic index.